2014
DOI: 10.15252/emmm.201404114
|View full text |Cite
|
Sign up to set email alerts
|

Specific roles for dendritic cell subsets during initiation and progression of psoriasis

Abstract: Several subtypes of APCs are found in psoriasis patients, but their involvement in disease pathogenesis is poorly understood. Here, we investigated the contribution of Langerhans cells (LCs) and plasmacytoid DCs (pDCs) in psoriasis. In human psoriatic lesions and in a psoriasis mouse model (DKO* mice), LCs are severely reduced, whereas pDCs are increased. Depletion of pDCs in DKO* mice prior to psoriasis induction resulted in a milder phenotype, whereas depletion during active disease had no effect. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 68 publications
8
103
1
Order By: Relevance
“…As pDCs have shown to control certain immune responses through the production of IFN-I, [7][8][9][10][11][12][13][14] we assessed the contribution of the IFN-I signaling to the control of the development of acute DSS-induced colitis using Ifnar1 À / À mice, which lacking IFN-a/b receptor I (IFNAR1). 34 Unexpectively, there was no substantial difference in the BW loss between WT and Ifnar1 À / À mice following oral DSS administration (Supplementary Figure S2a).…”
Section: Pdcs Accelerate Dss-induced Colonic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…As pDCs have shown to control certain immune responses through the production of IFN-I, [7][8][9][10][11][12][13][14] we assessed the contribution of the IFN-I signaling to the control of the development of acute DSS-induced colitis using Ifnar1 À / À mice, which lacking IFN-a/b receptor I (IFNAR1). 34 Unexpectively, there was no substantial difference in the BW loss between WT and Ifnar1 À / À mice following oral DSS administration (Supplementary Figure S2a).…”
Section: Pdcs Accelerate Dss-induced Colonic Inflammationmentioning
confidence: 99%
“…[7][8][9] Therefore, pDCs have been considered as important mediators of antiviral responses. [7][8][9] Furthermore, recent studies have suggested that the activation of pDCs by recognition of self-NA causes elevated IFN-I levels, 10 and this process contributes to the induction of pathogenesis in psoriasis 11 and systemic lupus erythematosus (SLE). [12][13][14] The intestine is the largest compartment of the immune system that is lined by a single layer of epithelium harboring commensal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Activated dermal cDCs concomitantly migrate to skindraining lymph nodes (LNs), where they trigger the differentiation of autoantigen-specific naive T cells into skin-tropic effector T cells that are capable of secreting TNF-a, IFN-g, IL-17, or IL-22 and responsible for fueling the late phase of psoriasis (2). These cytokines contribute to increase the numbers of infiltrating neutrophils and stimulate keratinocytes to produce growth factors and inflammatory mediators (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Blocking pDC-dependent pathological mechanisms in these situations has been mostly associated with remission, suggesting that mechanisms controlling pDC survival, such as IFN-I, might be unpaired (7,9). Several mechanisms have been described for the control of the inflammatory immune response working in concert or independently, such as the limitation of Ag presentation through the killing of APC.…”
mentioning
confidence: 99%